Model Integrasi Kurikulum Merdeka dan Kurikulum Cinta untuk Meningkatkan Efektivitas Pembelajaran PAI di SMP - Nur Af’idatul Jazilah; Jasminto Jasminto; Asriana Kibtiyah (CV. Creative Tugu Pena, 2026)
Islamic Religious Education (IRE) at the junior high school level still faces various challenges, such as a lack of internalization of religious values, social empathy, and religious moderation. This is due to the dominance of learning approaches that focus on cognitive aspects and memorization. The Merdeka Curriculum was introduced to provide flexibility and autonomy in the learning process, but it has not fully reached the affective dimension of students. Therefore, this study aims to examine the integration of the Merdeka Curriculum with the Cinta Curriculum as a humanistic, religious, and engaging approach to IRE learning. This study applies a qualitative method by combining a literature review and design-based research at the conceptual level. Data sources include education policy documents, Islamic education literature, and educational psychology journals. Data analysis was conducted using content analysis and comparative synthesis techniques. The results showed that the integration of the two curricula found similarities in the need for emotional security as a prerequisite for cognitive autonomy. The Merdeka Curriculum serves as a means of learning freedom, while the Cinta Curriculum provides a relational foundation through loving pedagogy. This integrative model encourages student participation in the learning process, internalization of moral values, and student psychological well-being. The main findings of this study emphasize that the success of PAI learning is highly dependent on the quality of the emotional relationship between teachers and students. This study recommends strengthening school policies that encourage the creation of a love-based and positive discipline educational environment.